1
$\begingroup$

According to Wikipedia, the $n$th cumulant $\kappa_n$ is related to the central-moments $\theta_n$ by the following recurrence:

$$\kappa_n = \theta_n - \sum_{m=1}^{n-1} \binom{n-1}{m-1} \kappa_m \theta_{n-m}$$

which allows one to compute the cumulants sequentially, given the central-moments. The Wikipedia page offers no reference or proof of this formula. What's the proof of this formula?

$\endgroup$
2
$\begingroup$

The equation given by Wikipedia connects cumulants to moments (generally).

A proof of a formula connecting cumulants to central moments is found in A Recursive Formulation of the Old Problem of Obtaining Moments from Cumulants and Vice Versa

Letting $K(t)$ be the cumulant-generating function, and $M(t)$ the moment-generating function. The relationship between the two is \begin{equation} M(t)=\exp{\left[K(t)\right]} \end{equation} The proof follows by differentiation of this expression and noting that the $n$th derivative can be written as \begin{equation} D^n[M(t)]=\sum_{i=0}^{n-1}\binom{n-1}{i}D^{n-i}[K(t)]D^i[M(t)] \end{equation} Where $D^k$ denotes the $k$th derivative. Now setting $t=0$: \begin{equation} \theta_n=\sum_{i=0}^{n-1}\binom{n-1}{i}\kappa_{n-i}\theta_i\\ \theta_n=\kappa_n+\sum_{i=1}^{n-1}\binom{n-1}{i}\kappa_{n-i}\theta_i\\ \end{equation} Rewriting yields: \begin{equation} \kappa_n = \theta_n-\sum_{i=1}^{n-1}\binom{n-1}{i}\kappa_{n-i}\theta_i \end{equation} In terms of the central moments and cumulants.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.